Teaching Internal Auditing at A University–An Example in Context. - Chambers, Andrew D. (The Accounting Review, 1978)
Abstract ABSTRACT: Though demands to teach internal auditing have now been made for over a generation, at present, internal auditing as a university discipline is in a serious decline. Indeed, the roots of the debate on internal audit education were recorded in THE ACCOUNTING REVIEW in the 1950s, and much of what is being said now is a restatement of old arguments. The principal issue of debate has been whether internal auditing should be taught. Internal auditing is flourishing in one university. This article suggests a number of reasons for its success, and questions established assumptions about internal audit education.